Training needs in the field of autism by contemporary Polish teachers in the context of international ASD-EAST project - Kossewska, Joanna; Preece, David; Lisak, Natalija; Bombińska-Domżał, Anna; Cierpiałowska, Tamara; Lessner Lištiaková, Ivana; Lubińska-Kościółek, Elżbieta; Niemiec, Sylwia; Płoszaj, Małgorzata; Stošić, Jasmina; Troshanska, Jasmina (Social Welfare: Interdisciplinary Approach, 2019)
The paper presents results of the part of international survey on teachers’ opinion on autism characteristics and specific educational approach and treatment. Research was undertaken in Poland under the auspicies of ASD-EAST project using quantitative and qualitative methods. The results showed the significant differences in teachers’ perception on autism regarding to the school settings they worked in. The strong need for special training in the field of ASD was also expressed by teachers.
Keywords: Autism spectrum disorder; inclusive education; teachers’ opinion on ASD characteristics; teachers’ training needs